Which of these answer choices is the factorization of ( a + b ) 7 − a 7 − b 7 ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Why and how did you choose the function f ′ ( a , b ) = 7 ( a + b ) 6 − 7 b 6 ?
Log in to reply
Because a b , ( a + b ) , ( a 2 + a b + b 2 ) are already factors of f ( a , b ) , and we have to determine the repeated factor.
To do so, we differentiate the function, in which case only repeated factors will still remain as factors.
E.g. we can check that f ′ ( 0 , b ) = 0 , f ′ ( a , − a ) = 0 , and so we can conclude that ( a b ) 2 ∣ f ( a , b ) and ( a + b ) 2 ∣ f ( a + b ) .
Log in to reply
SIr when you differntiadied the above function shouldn't there be 7a^6 in the expression. P.S:-i am just a beginner in calculus
Log in to reply
@Rishi Sharma – To clarify: he is only differentiating with respect to b . So a 7 vanishes after differentiation. It doesn't matter whether you differentiate with respect to a or b because it is a symmetric polynomial. That is, f ( a , b ) = f ( b , a ) .
Log in to reply
@Pi Han Goh – Right. The "proper" way to apply Remainder-Factor Theorem, is actually to use it for the one-variable case (which is the only time that it is always true).
So, by right, the polynomial that we should consider is f ( x ) = ( 1 + x ) 7 − 1 7 − x 7 and factorize that accordingly.
[I just didn't want to go into that for the solution, to avoid further confusion.]
( a + b ) 7 − a 7 − b 7 = a 7 + 7 a 6 b + 2 1 a 5 b 2 + 3 5 a 4 b 3 + 3 5 a 3 b 4 + 2 1 a 2 b 5 + 7 a b 6 + b 7 − a 7 − b 7 = 7 a 6 b + 2 1 a 5 b 2 + 3 5 a 4 b 3 + 3 5 a 3 b 4 + 2 1 a 2 b 5 + 7 a b 6 = 7 a b ( a 5 + b 5 ) + 2 1 a 2 b 2 ( a 3 + b 3 ) + 3 5 a 3 b 3 ( a + b ) = 7 a b [ ( a + b ) ( a 4 + b 4 ) − a b ( a 3 + b 3 ) ] + 2 1 a 2 b 2 ( a 3 + b 3 ) + 3 5 a 3 b 3 ( a + b ) = 7 a b ( a + b ) ( a 4 + b 4 ) + 1 4 a 2 b 2 ( a 3 + b 3 ) + 3 5 a 3 b 3 ( a + b ) = 7 a b ( a + b ) ( a 4 + b 4 ) + 1 4 a 2 b 2 [ ( a + b ) ( a 2 + b 2 ) − a b ( a + b ) ] + 3 5 a 3 b 3 ( a + b ) = 7 a b ( a + b ) ( a 4 + b 4 ) + 1 4 a 2 b 2 ( a + b ) ( a 2 + b 2 ) + 2 1 a 3 b 3 ( a + b ) = 7 a b ( a + b ) [ a 4 + b 4 + 2 a b ( a 2 + b 2 ) + 3 a 2 b 2 ] = 7 a b ( a + b ) ( a 2 + a b + b 2 ) 2
The remainder-factor theorem can be useful in this case to help us with this factorization.
Consider f ( x ) = ( 1 + x ) 7 − 1 7 − x 7 . Then, when ω is the complex cube root of unity, we have f ( ω ) = ( − ω 2 ) 7 − 1 7 − ω 7 = − ω 2 − 1 − ω = 0 . Hence, this tells us that ( x − ω ) divides f ( x ) and thus ( x 2 + x + 1 ) ∣ f ( x ) .
I also use this common factorization
How can we factorize this otherwise?
Yep. Who has the time to factorize? :P
Log in to reply
I will note something quite nice: we have that the multiplicity of p in the prime factorisation of ( k p ) is 1 exactly, which is why two of the options cannot be.
Problem Loading...
Note Loading...
Set Loading...
We will use the Remainder-Factor theorem to avoid expanding out all of the terms and trying to factorize them.
Consider f ( a , b ) = ( a + b ) 7 − a 7 − b 7 .
Since f ( 0 , b ) = 0 , this tells us that a ∣ f ( a , b ) .
Since f ( a , 0 ) = 0 , this tells us that b ∣ f ( b , b ) .
Since f ( a , − a ) = 0 , this tells us that a + b ∣ f ( b , b ) .
Since f ( a , ω a ) = 0 , this tells us that ( a 2 + a b + b 2 ) ∣ f ( b , b ) .
Thus, we have f ( a , b ) = C a b ( a + b ) ( a 2 + a b + b 2 ) × g ( a , b ) , where C is a constant and g ( a , b ) is a degree 2 symmetric polynomial. The possibilities of g ( a , b ) are a b , ( a + b ) 2 , ( a 2 + a b + b 2 ) .
Now, consider f ′ ( a , b ) = 7 ( a + b ) 6 − 7 b 6 . Once again, since f ′ ( a , ω a ) = 0 , hence we can conclude that ( a 2 + a b + b 2 ) ∣ f ′ ( a , b ) .
Thus, f ( a , b ) = C a b ( a + b ) ( a 2 + a b + b 2 ) 2 .
Finally, setting a = b = 1 , we get that C = 7 .